INISIASI CAMPING GROUND DI AREA SUNGAI LARANGAN: PAKET WISATA EDUKASI BERBASIS LINGKUNGAN DI DESA BILEBANTE, KECAMATAN PRINGGARATA, KABUPATEN LOMBOK BARAT, PROVINSI NUSA TENGGARA BARAT - Yustisio, Muhammad Desto; Jayadi, M. Nazir Ihsani; Novary, Tutur Anugerah; Saputri, Annisa Juniar; Royani, Bq. Sifa; Nisa’, Isna Masruratun; Rahmi, Erika; Udrayani, Ni Luh Ayu Sri; Permatasari, Rizky Indah; Kurniawan, Muhammad Rizki (Universitas Mataram, 2023)
A tourism village needs to develop attractions based on nature and education in order to become a sustainable tourism village. In Bilebante Village, the development of natural tourist attractions focuses on the Forbidden River area because of its beauty and a natural tourist destination that the community is proud of. The strategy that involves stakeholders through educational tours is to build a camping ground and several other programs. This community service activity is interested in the process of initiating a camping ground that has been planned for a long time by the tourism manager of this village. The process of making this camping ground uses open discussion method which involves all elements of society in Bilebante. The result is the provision of holding areas at river ban areas; creation of signposts to clarify tourists' activities during the camping period; and providing English lessons to increase the intensity of involvement of the Bilebante community, especially the younger generation. The results of this dedication had a positive impact on the development of nature-based and educational tourism in Bilebante Village evidenced by the creation of a camping ground in the Forbidden River area.